2011
DOI: 10.5152/eajm.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Compared with the Conventional MR Imaging, Do the Constructive Interference Steady State Sequence and Diffusion Weighted Imaging Aid in the Diagnosis of Lumbar Disc Hernias?

Abstract: Objective: Our aim was to evaluate the efficacy of Diffusion Weighted Imaging (DWI) and Constructive Interference Steady State(CISS) sequences in the depiction of lumbar disc hernias, including sequestrated and extruded discs. Materials and Methods: 100 patients; 35 males and 65 females, with 3 sequestration -16 extruded and 81 protruded all together 100 herniated discs were involved in this study. If a patient had more than one herniated disc, then the more precise herniation was included. All the MRI procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This range of results is likely representative of the diferent levels of radiological experience and diferent backgrounds between the 15 In people, the CISS sequence has been shown to be highly sensitive and speciic in the evaluation of lumbar disc herniations, especially for the extruded and sequestrated discs. 16 Although this sequence cannot diferentiate properly disc material from osteophytes, it easily revealed the site of injury and relationship of the herniated fragment to the dural sac, nerve roots and bulged discs. 1 In our study, although the intraobserver agreement between T2W and CISS sequences for nerve root compression was moderate to substantial, in some studies the T2W was insuicient for detailed analysis of nerve roots, especially in cases of disc herniation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This range of results is likely representative of the diferent levels of radiological experience and diferent backgrounds between the 15 In people, the CISS sequence has been shown to be highly sensitive and speciic in the evaluation of lumbar disc herniations, especially for the extruded and sequestrated discs. 16 Although this sequence cannot diferentiate properly disc material from osteophytes, it easily revealed the site of injury and relationship of the herniated fragment to the dural sac, nerve roots and bulged discs. 1 In our study, although the intraobserver agreement between T2W and CISS sequences for nerve root compression was moderate to substantial, in some studies the T2W was insuicient for detailed analysis of nerve roots, especially in cases of disc herniation.…”
Section: Discussionmentioning
confidence: 99%
“…In people, the CISS sequence has been shown to be highly sensitive and specific in the evaluation of lumbar disc herniations, especially for the extruded and sequestrated discs 16 . Although this sequence cannot differentiate properly disc material from osteophytes, it easily revealed the site of injury and relationship of the herniated fragment to the dural sac, nerve roots and bulged discs 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Tins et al [2] claimed that a 3D SPACE sequence in conjunction with sagittal T1W images was sufficient for routine spinal imaging with increased diagnostic confidence. Aydin et al [12] studied a CISS sequence, which is a gradient-echo technique with steady-state free precession, and quantitative diffusion-weighted imaging for routine lumbar disc imaging, and the authors found that these sequences may be alternative imaging approaches to conventional MRI approaches for assessing lumbar disc hernias [12].…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 When contrast media is used, which has not been done in our case, a ring enhancement of the herniated portion can be seen, caused by granulation tissue. 1–5 While 3D CISS sequence performance is similar to standard T2-weighted images for the depiction of extradural lumbar disc herniation, 6 the use of 3D high-resolution CISS sequence in IDH has not been reported yet. However, several studies have demonstrated the potential of 3D high-resolution CISS to assess other intradural diseases such as redundant nerve root syndrome of the cauda equina 7 or thoracic anterior spinal cord adhesion syndrome.…”
Section: Discussionmentioning
confidence: 99%